MANAGING INTERNATIONALIZATION AT HIGHER EDUCATION INSTITUTIONS: ASSIGNED DRIVERS AND PERCEIVED IMPORTANCE - Katarina Askerc Zadravec (Agora International Journal of Economical Sciences (AIJES), 2023)
The internationalization of higher education has become a central focus in contemporary higher education policies, where various demands, motives, and meanings are attributed to higher education institutions and management in the global and international environment. The complex relationship between globalization and internationalization is briefly explored in the article, as well as motives and drivers for the internationalization of higher education at both national and institutional levels, with university management considering it a strategic priority. Through semi-structured interviews with representatives of Slovene higher education stakeholders, it was found that university management emphasizes the significance of internationalization as a strategic priority and as part of the university's daily activities, highlighting its integration into research, education, various networks, projects, etc. The article underscores that internationalization serves as a means and driver for changes, raising quality, improvements, employability, and innovations in higher education, fostering a knowledge-based society, and addressing the challenges of the globalized world, which were highlighted by the respondents. In the final part of the article, suggestions for improvements and further research activities are presented.
Keywords: 330